The US Constitution of 1791 and the Fugitive Slave Clause : a philosophical re-rendering of legislative authority : ambiguities and conflicts /: a philosophical re-rendering of legislative authority : ambiguities and conflicts. (2019) - Coles, Norman A, 1939-
No abstract available